Determinação multiclasse de agrotóxicos em camas biológicas empregando cromatografia líquida acoplada a espectrometria de massas - Jänisch, Bárbara Diana (2022)
Pesticides are used worldwide in the agricultural production of different crops in order to avoid losses in production due to the attack of pests and diseases. Due to the increase in food production, consequently, the concern about the correct disposal of pesticide residues is growing. Thus, from 1990 onwards, biobeds began to be developed in order to reduce contamination from accidental spills during pesticide formulation dissolution and in the washing of sprayers. The biomix, made up of soil, straw and peat, which makes up the biobeds, is primarily responsible for retaining and biodegrading pesticides. Among those different classes of pesticides, herbicides represent a large percentage (59,56%) of the most sold active ingredients in Brazil. Therefore, the meangoal of this study was to develop and to validate two extraction methods for pesticide determinations. A multiclass method composed of five distinct classes of herbicides, in addition to an insecticide class and an individual method, for the imidazolinone class herbicides, in the biomix that compose biobeds and its determination applying HPLC-MS/MS. To evaluate biobeds efficiency through the contamination of reactors, with those active ingradients under study and verifying their degradation over time with collections and subsequent analysis at different times, was also a goal in this project. To method validation studies, the criterias of linearity, linear range, matrix effect, limit of detection (LD) and limit of quantification (LQ), precision, intermediate precision and accuracy were evaluated. For those pesticides determined via individual method, imazapic and imazethapyr, the detection and quantification limits were 12.5 μg kg -¹ and 20 μg kg -¹ respectively. For all pesticides determined via multiclass method, 2,4-D, acetochlor, atrazine, diuron, dicamba and methidathione, the LOD was 8 μg kg -¹ and LOQ 20 μg kg -¹. The positive matrix effect for the imidazolinone extraction method was very evident by comparing the analytical curves data, prepared in organic solvent and in blank matrix extract, because the biomix is a very complex matrix and the extraction procedure has a high pH variation, which influences the interferents co-extraction. The analysis of biomix samples from contaminated biobeds showed that most of pesticides (2,4-D, atrazine, diuron, methidathione) under study were degraded. The exception was for imazethapyr, which possibly due to its known persistence in environment and dependence on specific conditions to be available and to be biodegraded, was not degrated. Further more, dicamba presented a lower biodegradation compared to other pesticides, that may be due to interactions with other pesticides discharged in to the biobed.